2018
DOI: 10.1515/pac-2017-0804
|View full text |Cite
|
Sign up to set email alerts
|

Composites containing bamboo with different binders

Abstract: We have obtained composites on the basis of dry bamboo powders and in turn several binders, including polyethylene (PE) and alkoxysilanes. The composites were studied by Fourier transformation infrared spectroscopy (FTIR), optical and scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Some mechanical properties were determined along with thermal stability by thermogravimetry; water absorption was also determined. FTIR results show formation of primary chemical bonds between bamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Siloxanes can not only serve as solvents but also as electrolyte additives which could participate in the interfacial film forming processes at both cathode and anode surfaces. [80][81][82][83] It was reported that the thermal stability of cathode charged in the siloxane electrolyte was superior to that in the carbonate-based electrolyte. [84] Siloxane electrolytes were also demonstrated particularly suitable for carbonaceous electrode materials by forming a passive film at the electrode/electrolyte interface.…”
Section: Micromolecule Silane and Siloxanementioning
confidence: 99%
“…Siloxanes can not only serve as solvents but also as electrolyte additives which could participate in the interfacial film forming processes at both cathode and anode surfaces. [80][81][82][83] It was reported that the thermal stability of cathode charged in the siloxane electrolyte was superior to that in the carbonate-based electrolyte. [84] Siloxane electrolytes were also demonstrated particularly suitable for carbonaceous electrode materials by forming a passive film at the electrode/electrolyte interface.…”
Section: Micromolecule Silane and Siloxanementioning
confidence: 99%
“…Wood sawdust impregnated with TEVPES and styrene, at the moment of hot pressing, forms chemical bonds with the hydroxyl groups of a wood surface. Active filler is likely formed, then etherification 31,32 and in-situ polymerization reactions take place.…”
Section: Resultsmentioning
confidence: 99%
“…During hot-pressing, the initiator existing in the mixture may initiate the polymerization reaction of vinyl groups of triethoxysilylated styrene. 28,29 Wood sawdust impregnated with triethoxysilylated styrene, at the moment of hot pressing, forms chemical bonds with the hydroxyl groups of cellulose. Active filler is likely formed, then etherification and polymerization reactions take place.…”
Section: Resultsmentioning
confidence: 99%
“…We see that the lowest water absorption is characteristic for composites containing the optimal (5 wt%) of the binder and created at high pressing temperatures -in agreement with some results reported earlier. 28,29 In Fig. 4 we show the dependence of water absorption on the binder concentration.…”
Section: Water Absorptionmentioning
confidence: 99%